The Current Status and Advance in Treatment of Glycogen Storage Disease Type Ⅰb - JIANG Jingjing; MA Mingsheng (罕见病研究)
Glycogen storage diseases (GSDs)refer to a group of metabolic disorders caused by congenital enzyme deficiencies. This group of diseases are characterized by abnormal glycogen metabolism. Most subtypes can lead to increased glycogen accumulation in tissues of the liver, muscles, kidneys etc. GSD type Ⅰ (GSDⅠ) is the most common type of the liver glycogen storage diseases that are caused by a deficiency in glucose-6-phosphatase in the liver, kidneys, and intestines. This typle has two subtypes: type Ⅰa and type Ⅰb(GSDⅠb). Recently, research into the molecular mechanisms of GSD Ⅰb made further progress, leading to significant improvements in clinical diagnosis and the new treatment methods based on the pathogenesis. This article summarizes the current research status of diagnosis and screening, molecular genetic mechanisms, and treatment of GSD Ⅰb. The article also points out the opportunities, the challenges and future possibilities.